Kahoot ; a Digital Learning Platform to Improve Vocabulary and Grammar Skills - Lestari, Puji; Sihombing, Lambok Hermanto (Universitas Islam Balitar, 2022)
English is a global language. It is also a subject that must be taught in educational institution especially schools in Indonesia. There is a lot of teaching methods that can teachers apply in making the students interested in learning its language. One of them is through online game namely Kahoot. This study aims to analyse how Kahoot becomes a learning platform that can help students improve their English skills. To assist the authors in doing this analysis, the Teaching Principle theory by H. Douglas Brown and Heekyong Lee was applied in this study. The authors implemented qualitative approach. The subject of the study is the students of Binakarya Mandiri Vocational High School in Bekasi specifically the English Club students. Aside from it, the authors also took the data from any supporting articles. The findings show that they could improve their English skills especially vocabulary and grammar from Kahoot as digital learning platform.